Evaluating the 1990 projections of occupational employment. - Rosenthal, Neal H. (Monthly Labor Review, 1992)
The occupational projections of the Bureau of Labor Statistics (BLS) for 1990 were conservative. Although total employment for 1990 was projected accurately, too many occupations were projected to have average growth. In addition, most of the occupations expected to have rapid growth were underprojected. An evaluation of the BLS occupational projections is presented. Tables present statistics comparing projected and actual 1990 employment in selected occupations.